Компартменты паренхимы лимфатических узлов у новорожденных особей быка домашнего (Bos taurus) - Гаврилін, Павло Миколайович; Gavrilin, P.; Gavrilin, P. N.; Gavrylin, P.; Gavrylin, P. M.; Havrylin, P. M.; Havrylin, P.; Gavrilin, Pavlo; Gavrilin, Pavel; Gavrilin, P. M.; Гавриліна, Олена Геннадіївна; Gavrilina, O.; et al. (Oles Honchar Dnipropetrovsk National University, 2017)
Проанализированы особенности строения компартментов (лимфоидных долек) в паренхиме различных групп лимфатических узлов у новорожденных особей быка домашнего. Для одновременной визуализации структурных компонентов лимфоидных долек использовали авторскую модификацию импрегнации тотальных срединных замороженных срезов азотнокислым серебром. Лимфоидная паренхима всех групп лимфатических узлов имеет выраженную дольчатую структуру. Компоненты лимфоидных долек подразделяются на два основных морфотипа. Первый морфотип представлен лентообразными перисинусоидальными тяжами (интерфолликулярная зона, паракортикальные и мозговые тяжи), которые обеспечивают миграцию лимфоцитов, детекцию антигенов и аккумуляцию плазмоцитов. Второй морфотип представлен округлыми образованиями (центральные зоны единиц глубокой коры или Т-зависимые зоны, лимфатические узелки или В-зависимые зоны), отвечающие за клональную пролиферацию лимфоцитов. Относительный объем структур первого морфотипа в 4,5–8,0 раз превышает объем структур второго морфотипа. Структуры первого морфотипа развиты относительно равномерно топографически нестабильными компонентами лимфоидных долек, формируються на основе всех видов тяжей лимфоидной паренхимы, и, в том числе, мозговых тяжей висцеральных лимфатических узлов. The article analyzes the features of the structure of the lymphoid lobules of the parenchyma of the superficial somatic (Limphonodi subiliaci, L. cervicales superficiales), profund somatic (L. axillares proprii L. poplitei), somatovisceral (L. iliaci mediales, L. retropharyngei mediales) and visceral (L. mediastinales caudales, L. ileocolici) lymph nodes of newborn bull calves of domestic cattle. To visualize clearly the boundaries of the structural components of lymphoid lobules we used the author’s modification of the impregnation of total median frozen histological sections with silver nitrate. We have established a high level of tissue differentiation of the lymph nodes, a significant development of the lymphoid parenchyma, the division of the parenchyma into lymphoid lobules, the presence in the lobules of all the main structural components that are represented by two morphotypes. The first morphotype is ribbonlike perisinusoidal cords (interfollicular zone, paracortical and medullary cords). The second morphotype is rounded lymphoid formations (central zones of deep cortex units, lymphatic nodules). Lymphoid lobules are located along the marginal sinus in one row, they are better developed and differentiated in the visceral lymph nodes. In all the lymph nodes, the lymphoid lobules have a similar histoarchitectonics, and each structural component of the lymphoid lobules has a specific architectonics of the reticular meshwork and the density of the location of the fibroblastic reticulocytes. We determined that the structures of the first morphotype which provide the migration of lymphocytes, the detection of antigens and the accumulation of plasmocytes are more developed. We have established that the relative volume of structures of the first morphotype is 4.5–8.0 times larger than the volume of the structures of the second morphotype, which provide clonal proliferation of T and B lymphocytes, especially in deep somatic lymph nodes. Among the zones of the second morphotype, predominate T-dependent zones, the relative volume of which considerably exceeds the volume of B-dependent zones (lymphoid nodules): in the superficial somatic lymph nodes by 14–30 times, profound somatic by 12–14 times, somatovisceral by 6–7 times and visceral by 4.5–5.5 times. We determined that lymphatic nodules can form in different parts of compartments: in the interfollicular zone and paracortical cords of all lymph nodes and in the medullary cords of the visceral lymph nodes. The study shows that the parenchyma of the lymph nodes of newborn bull calves has a high degree of maturity, contains a full set of structural markers of immunocompetence, among which predominate the components that support lymphocyte migration, antigen detection and accumulation of plasma cells.
The compartments of the parenchyma of the lymph nodes in the newborn bull calves of domestic cattle (Bos taurus)
Гаврилін Павло Миколайович http://orcid.org/0000-0003-3386-1475 Гавриліна Олена Геннадіївна http://orcid.org/0000-0001-9624-9510
Keywords: лімфоїдні вузлики; lymphoid nodules; лімфоїдні часточки; lymphoid lobules; одиниці глибокої кори; deep cortex units; паракортикальні і мозкові тяжі; paracortical and medullary cords